MUDHARABAH FINANCING AND MUSYARAKAH FINANCING APPLICATIONS AT BANK JATENG SYARIAH - Efi Fajar Arifin; Siti Afidatul Khotijah (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2023)
According to the provisions of Law Number 21 of 2008 regarding sharia banking, sharia banks are defined as banking institutions that are subject to the same legal regulations as conventional banks, but in their operational activities, they follow the principles of Islamic sharia. As the banking sector continues to develop, competition becomes increasingly fierce, and every bank must provide quality service and add types of products desired by customers. This study examines the application of sharia accounting for mudharabah and musyarakah financing in Bank Jateng Syariah based on PSAK No. 105 and PSAK No. 106. Sharia banks are subject to the same legal regulations as conventional banks, but their operational activities follow Islamic sharia principles.The discussion focuses on the practice of mudharabah and musyarakah financing at Bank Jateng Syariah. This study uses a qualitative descriptive method by using data from published financial reports. The results show that the application of mudharabah and musyarakah financing in Bank Jateng Syariah is in accordance with PSAK No. 105 and PSAK No.106, with various adjustments made to the provisions issued by the Financial Services Authority.